Arthur Leon Campa, Spanish folk-poetry in New Mexico. Albuquerque, The University of New Mexico Press, 1946, 224 págs. - Mejía Sánchez, Ernesto (Nueva Revista de Filología Hispánica (NRFH), 1949)
Se reseñó el libro: Spanish folk-poetry in New Mexico.